Freeze–Thaw damage characteristics of composite modified open graded friction course - Qi, Lin; Yu, Baoyang; Song, Jingang; Zhang, Chunshuai (Frontiers in Materials, 2022)
To reasonably describe the damage characteristics of composite modified open graded friction course (OGFC) after multiple freeze–thaw cycles, based on the Able viscoelastic constitutive equation, a viscoelastic model of freeze–thaw damage was constructed and analyzed using the Weibull distribution function, damage mechanics, and fractional derivative theory. Under the conditions of composite modified OGFC mixtures with different mixing ratios (12%, 0%), (12%, 1%), and (12%, 2%), and multiple freeze–thaw cycles (0–16), low-temperature bending and creep tests of the mixtures were carried out. The stress–strain curve data obtained were fitted to analyze the physical significance of the model parameters. The results show that the model is suitable for characterizing the viscoelastic stage of composite modified OGFC under 10 freeze–thaw cycles. The freeze–thaw damage model parameters of three types of composite modified OGFC with different mixing ratios were compared and analyzed. The order of the fractional derivative of the composite modified OGFC model (12%, 1%) was 0.2223, the maximum damage threshold was 1.108, and the maximum viscosity coefficient was 371.84. This composite modified OGFC had the best low-temperature crack resistance.